Analysis of the Digital Based Education Budgeting Process in the Management of School Operational Assistance Funds - Rita Nurhayati; S Martono; Dwi Cahyaningdyah (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to analyze the education budgeting process at the elementary school level, focusing on the management of regular School Operational Assistance (BOS) funds at Jlegong 1 Public Elementary School. The study focuses on the budget planning, implementation, and accountability mechanisms integrated through the digital School Activity and Budget Plan Application (ARKAS) and the School Procurement Information System (SIPLAH). Fund management is handled by the treasurer and BOS administrator under the principal's supervision, with input from the school committee and parents serving as advisors. This study uses a qualitative descriptive approach, relying on observation, interviews, and documentation for data collection. The findings show that adopting a digital system enhances the accuracy, efficiency, and transparency of school financial reports. Nonetheless, some challenges arose, particularly in data synchronization and the limited technical skills of the operators. Overall, participatory and data-driven budgeting strengthens accountability and improves the effectiveness of financial governance in elementary schools. Keywords: Digital Educational Budgeting, School Financial Management.